Sufistik Cinta dalam Al-Qurâ€™an: Kajian Semantik - Lazulfa, Haiyin Lana; Munir, Ahmad (Jurnal Riset Agama, 2022)
This study aims to discuss the sufistic love of the Qur'anic perspective with a semantic approach. Thiselitisting uses a qualitative approach by applying descriptive-analytical methods. The formal object of this study is semantic studies. Meanwhile, the material object in this study is sufistic love of the perspective of the Qur'an. The results of this research and discussion show that the semantic approach can help present and understand the meaning contained in the Qur'an whose original ideas were fragmented to achieve a totally unified idea (its worldview). Love (hubb) is divided into three parts, namely the love of Allah Swt., to man, the love of man to Allah Swt., and the love of man to his fellow human beings, all three of which have been clearly stated in several verses of the Qur'an. The conclusion of this study is that the true love of the faithful will rightly only be to God that they pour out all their lives that will turn the muhibbin Â away from everything but the one he loves.